Leadership styles of men and women in the SMES (2017)
Different leadership styles are exercised according to the gender (male or female). On the one hand, women have been regarded as more transformational individuals than men, who, on the contrary, are considered more transactional. In this regard, this study identifies the leadership style promoted according to the manager’s gender in the SMES of the manufacturing and high technology sector in Cali. To this end, the Multifactor Leadership Questionnaire (MLQ) is applied to a probability sample of 142 managers. The results show that the transformational style predominates in the SMES for both men and women. Therefore, there is no meaningful difference between the leadership style of both. This research contributes to a new context in which the leadership style does not vary on the basis of gender, and it raises the idea that both men and women can lead similarly.